(untitled) (Journal of Pharma Insights and Research, 2025)
Molecular markers are valuable genetic tools that have revolutionized pharmaceutical research and development. The rapid advancement in molecular genetics has led to the advent of various marker systems, from traditional morphological and biochemical markers to sophisticated DNA-based technologies. These genetic markers serve as powerful tools in pharmacogenomics, drug discovery, personalized medicine, and quality control of pharmaceutical products. The evolution of marker technologies spans from Restriction Fragment Length Polymorphisms (RFLPs) to modern high-throughput systems like Single Nucleotide Polymorphisms (SNPs) and Next Generation Sequencing platforms. Each marker system offers unique advantages in specific applications, such as drug target identification, genetic disease diagnosis, and authentication of herbal medicines. Molecular markers have become instrumental in developing companion diagnostics, optimizing drug dosages, and predicting adverse drug reactions through genetic profiling. The use of molecular marker data with artificial intelligence and machine learning has opened new avenues in drug development and clinical decision-making. Despite their numerous advantages, challenges exist in terms of cost, technical expertise requirements, and data interpretation. The marker technologies with advances in bioinformatics and sequencing methods, positions molecular markers as essential tools in modern pharmaceutical sciences.